PENGARUH KUALITAS PRODUK, HARGA, PROMOSI DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR HONDA JENIS BEAT PADA PT. KELIMUTU ABADI MOTOR - Watu, Fiktorianus; Se, Hyronimus; Laga, Yulius (SCIENTIFIC JOURNAL OF MANAGEMENT AND BUSINESS (SJMB), 2021)
This study aims to determine the effect of product quality, price, promotion, and quality of service on the decision of motorcycle buyers Honda Beat. The type of research used is causality research with quantitative approach. The data analysis technique used is analysis multiple linear regression. The population in this study consisted of 570 respondents and a sample of 57 respondents obtained using a simple technique random sampling. From the results of the development and testing of the instrument has been produced a qood questionnaire tool (qualifies validity and reliability). From result t statistical test for the variables of product quality, price, promotion and quality service has a value > significance valye < 0,05. This matter shows that the variables of prduct quality, price, promotion and quality service has a significant effect on purchasing decisions. For value adjusted R square of 0,518, this shows that the percentage of the variable product quality, price, promotion and service quality on decisions purchases of 51,8%. While the rest is influenced by other factors that not described in this stidy